Exploring tomato phenotypic variability under combined nitrogen and water deficit - Machado, Joana; Heuvelink, Ep; Vasconcelos, Marta W.; Cunha, Luís M.; Finkers, Richard; Carvalho, Susana M. P. (Plant and soil, 2024)
Background Despite drought and nitrogen (N) deficit being two of the most important crops’ growth limiting factors, only few studies have explored tomato phenotypic variability in response to both abiotic stresses. Aims In this study, we aimed to perform a phenotypic evaluation and an analysis of the growth traits of 40 tomato genotypes (mostly focusing on old cultivars, but also including modern hybrids and wild tomato relatives’ accessions as anchors) grown in pots that were subjected to combined N and water deficit. Methods Each genotype was divided into two groups: control (100% N, 100% field capacity) and combined deficit (20% N, 50% field capacity). A total of 14 morpho-physiological traits were evaluated and further analyzed using multivariate statistical methods. Results The Principal Component Analyses revealed considerable phenotypical diversity among tomato genotypes, with four principal components explaining 82% of the variability. Data integration on a cluster analysis separated the studied genotypes into three distinct clusters based on their ability to handle the combined deficit. Tolerance was associated with traits such as lower specific leaf area, lower leaf area ratio and higher water use efficiency, comparing to the sensitive genotypes. Conclusions This study shows that tomato tolerance to combined N and water deficit largely varies between genotypes and that old cultivars represent a valuable gene pool towards more sustainable food production systems.